Efektivitas Model Pembelajaran Inkuiri Terbimbing Berbantuan Media Animasi terhadap Motivasi Belajar dan Kemampuan Berpikir Tingkat Tinggi Siswa dalam Pembelajaran Geografi SMA - Romiati Navlida Situmorang; I Putu Sriartha; I Gede Putu Eka Suryana (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to analyze the effectiveness of guided inquiry learning model assisted by animation media on students' learning motivation and high-level thinking skills in geography learning. This study was conducted at SMA Negeri 1 Seririt with subjects of grade XI students. The experimental class and control class were selected using simple random sampling techniques from equivalent pairs based on previous equivalence tests.The research design used was pretest-posttest nonequivalent control group design. The research sample was a pair of equivalent classes, namely class XI 8 consisting of 34 students as the experimental class and class XI 5 consisting of 33 students as the control class. Data collected through observation, tests, questionnaires, documentation. Research data were analyzed descriptively quantitatively. The results of the study showed that: (1) The implementation of the guided inquiry learning model assisted by animation media in geography learning can be applied with very good criteria (88.75), (2) The guided inquiry learning model assisted by animation media is classified as effective in increasing student learning motivation with an experimental class N-Gain index of 0.69> control class N-Gain index of 0.091; and quite effective in increasing students' high-level thinking skills with an N-Gain index of 0.65> control class N-Gain index (0.13). The results of this study have implications for the importance of promoting the application of guided inquiry learning models assisted by animation media to geography teachers to improve students' learning motivation and also students' high-level thinking skills in geography learning.